School turnaround in secondary schools : possibilities, complexities, and sustainability - Meyers, Coby V.; Darwin, Marlene (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2020)
"In the continuing quest to turnaround the lowest performing schools, rapid and sustainable reform, or school turnaround, seems most elusive for secondary schools. Secondary schools are rife with challenges due to their wide-ranging mission and organizational complexity. With the continued emphasis on college and career readiness and the vast learning possibilities enhanced by technology, our third book in this series, Contemporary Perspectives on School Turnaround and Reform, focuses on rapid school turnaround and reform in secondary schools. In this edited volume, researchers and scholars consider the doubly perplexing challenge of school turnaround or the rapid improvement of the lowest-performing secondary schools. Although there is some evidence that school turnaround policy can impact student achievement scores, research across international contexts seldom identifies schools that substantially changed student learning trajectories and sustained them. Separately, many societies have found improving secondary schools a relatively intractable problem for multiple reasons, including school size and complexity, the micropolitics of teaching and leading within them, and cumulative widening student achievement gaps. In combination, there are almost no examples of low-performing secondary schools turning around. The chapters in this book begin to offer some hope about how policymakers, practitioners, and researchers might begin to reconceptualize how they engage in and undertake the work of rapidly improving low-performing secondary schools. The authors provide theoretical and conceptual advancements, offer lessons learned from both successful and unsuccessful initiatives, and address practical issues with potentially accessible ways forward"-- Provided by publisher.
Keywords: Education, Secondary -- Aims and objectives -- Case studies.; School improvement programs -- Case studies.; Low-performing schools -- Case studies.; Educational change -- Case studies.; elektronické knihy; Case studies.; Education -- Educational Policy & Reform -- Federal Legislation.; Educational administration and organization.; Educational strategies and policy.; Central, national, federal government policies.; electronic books